Pelatihan Khusus Pancing Batang Ikan untuk Usia Produktif di Kalangan Pemuda Desa Jambur Pulau Kecamatan Perbaungan - Hatta Ridho; Husni Thamrin (Universitas Medan Area, 2022)
Fishing is an activity to catch fish which can be a livelihood, sport, or hobby that is carried out on the edge or in the middle of the sea, rivers, lakes and other waters. Fishing activities can be a leisure activity or a means of weekend recreation and a means of channeling hobbies. The fans come from various upper classes, middle and lower classes and fishing can be done by anyone, from teenagers to the elderly, both men and women can do fishing activities. Technology advances, fishing rods are made of high-tech materials and have better strength. In addition, these materials are lighter and more sensitive. Along with the times and the impact of the Covid-19 pandemic, fishing activities are increasingly popular, and the emergence of various fishing communities in various places, therefore training is needed to make fishing rods for independence and open business opportunities for young people of productive age. Partners in community service with the Mono-Year Partnership scheme have the output targets of scientific publications, mass media publications, increasing competitiveness, and increasing the application of science and technology. The methods used in this program are socialization to increase understanding about fishing and fishing gear, training in making custom fishing rods and providing operational support assistance.